The effect of ultraviolet treatment on enzymatic activity and total phenolic content of minimally processed potato slices - Li, Shing Teoh; Ola, Lasekan; Mohd Adzahan, Noranizan; Hashim, Norhashila (Transstellar Journal Publications and Research Consultancy Private, 2016)
In this work, potato slices were exposed to different doses of UV-C irradiation (i.e. 2.28, 6.84, 11.41, and 13.68 kJ m-2) with or without pretreatment [i.e. ascorbic acid and calcium chloride (AACCl) dip] and stored at 4 ± 1 °C. Changes in enzymatic activities of polyphenol oxidase (PPO), peroxidase (POD) and phenylalanine ammonia lyase (PAL), as well as total phenolic content (TPC) were investigated after 0, 3, 7 and 10 days of storage. Results showed that untreated and UV-C treated potato slices at 13.68 kJ m-2 dosage level showed significantly higher PPO, POD and PAL activities. Conversely, untreated potato slices showed the lowest TPC during storage period. Potato slices subjected to AACCl dip plus UV-C at 6.84 kJ m-2 produced lower PPO, POD and PAL activities, as well as maintained a high TPC during storage.